Understanding training? Posttranscriptional regulation of training adaptation - Bloch, W. (2018)
Vortrag auf der 2018 World Rowing Sports Medicine and Science Conference, 21.-23. November in Berlin. The presentation amongst others is on posttranscriptional processes induced by physical training und regeneration, mRNA stability and availability, the release of miRNA in dependence from trainings protocol, mechanisms of fast loss of muscle power - Loss of speed; posttranslational regulation /protein modulation, fast calclium regulation a principal for fast muscle contraction, nitric oxide (NO) for additional post transcriptional modulation of calcium release and myofilaments, free radicals (ROS and NO) and post translational modification, skeletal muscle growth and maintenance, dynamic of S6 phosphorylation, comparison of hypertrophy, eccentric, concentric resistance training in relation to muscle changes and induction of autophagy, ECM processing